ʻAqīdah-yi Ḵẖilāfat-i Rāshidah aur imāmat - Ḥusain, Qāzī Maẓhar (Taḥrīk-i Ḵẖuddām-i Ahlussunnat val-Jamāʻat, Multān Ḍivīzhan, 1988)
Critical study of the Shia beliefs about the caliphate and imamate in Islam; by a Sunnite scholar.